Altar Radiances among the Ritual Objects of Armenian Church (On the Example of the Collections of Armenian Diocese of Romania) - Vardanyan, Mariam R. (Actual Problems of Theory and History of Art, 2023)
A radiance is one of the elements of decoration of the Holy Table, typical exclusively for the Armenian Apostolic Church. It was formed under the influence of the Western Church tradition perhaps after the 17th century, served from western monstrance or ostensorium as an example. The fact that Armenian Church adopted the object much later testifies to its non-ritual function. The radiance usually represents round or oval metal compositions framed by rays, decorated from one side or from both sides. The center usually depicts either the Crucifixion of Christ or the Madonna with the Child. The Radiances preserved in Romania are mostly of local origin and were created during the 19th century. The design of these objects, obviously, was influenced by local culture, signs of which particularly are the scenes decorating the object, as well as their iconography. To a large extent, the masters remain unknown, but it is undeniable, that all the examples were made for the Armenian patrons of the Church, since the Romanian Church did not use objects of this type. The collection of altar radiances from the Armenian Diocese of Romania is of great importance, since it is distinguished by the diversity of the object. It is also worth mentioning the discovery of an engraved inscription on one of the items containing the name of one of the Armenian silversmiths who worked in Romania in the end of the 18th and the beginning of the 19th century. This study became possible by the support of the Diocese of Armenian Church in Romania, Ministry of Culture of RA and State Committee of Science MES RA, in frames of the research project No. SCS 13-6E440.